Análise da fragmentação de áreas de vegetação natural e semi-natural do município de Santa Cruz da Conceição, São Paulo, Brasil - Fushita, Angela Terumi (2006)
Habitat fragmentation has three major components, namely loss of the original area and reduction in size and increasing of patches. This process was helped with the development of biogeography theory, metapopulation dynamic and sink and source model. This study analyzed the landscape dynamic of the municipality of Santa Cruz, São Palo State, Brazil to base the public politics elaboration. The land occupation was classified in 1962, 1972 and 2002 based in aerial photographic because this material is more accurate than satellite images. Several softwares were used and they had allowed to make the treatment of satellite image and aerial photographic treatment until the analysis of some landscape metrics. We made thematic maps of the municipality. The natural and semi-natural areas were separated and were analyzed the Area/density/edge, Shape, Core Area, Isolation/Proximity and Edge Contrast to each class of fragments in software Fragstats 3.3. The Relative Ecological Vulnerability (REV), Connectivity and Shape were analyzed in MapInfo 7.5. The results indicated that the deforestation was faster before 1962. The lost of cerrado, fields and flooded areas happened between 1962 and 1972 and the recovering of riparian zone happened between 1972 and 2002. The matrix was pasture in 1962 and 1972 and was pasture and sugar cane fields in 2002. In the 1962 there were more fragments but they were smaller and had more edge than in the other examined years. The patches had simple shape and were less isolated in 1962 and 1972. The number of source fragments was greater in 2002. In future, aiming the conservation of remaining natural areas, should be fostered the increase of fragments area and the vegetation recovering in permanent preservation area, as well as key sites for organisms dispersion that may improve the exchange of individuals among reserves. These actions should improve landscape integrity.